2001
DOI: 10.1017/s1030011200024842
|View full text |Cite
|
Sign up to set email alerts
|

The Post School Outcomes of Young Adults with Autism Spectrum Disorder

Abstract: This study presents a broad picture of the post school outcomes of 28 young adults with Autism Spectrum Disorder living in South Australia. Findings from the study suggest that the majority of the participants still have a long way to go to reach the goal of meaningful participation in the economic and social life of their local communities. Most of the young adults had limited social networks and were highly dependent on their families for tangible and emotional support. While many of the participants were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The sample size is reasonable, considering Australia's low overall population, the relatively uncommon nature of the target population, and the smaller sample sizes reported in much of the literature (e.g., Burrows et al, 2001;Camarena & Sarigiani, 2009;Taylor & Seltzer, 2011). The willingness of so many parents to participate and their enthusiasm for doing so likely reflects the importance they place on post-school issues and service needs.…”
Section: Servicementioning
confidence: 99%
See 1 more Smart Citation
“…The sample size is reasonable, considering Australia's low overall population, the relatively uncommon nature of the target population, and the smaller sample sizes reported in much of the literature (e.g., Burrows et al, 2001;Camarena & Sarigiani, 2009;Taylor & Seltzer, 2011). The willingness of so many parents to participate and their enthusiasm for doing so likely reflects the importance they place on post-school issues and service needs.…”
Section: Servicementioning
confidence: 99%
“…In contrast, in Japan over 92% of adults with high-functioning ASD reportedly live with their families (Kamio, Inada, & Koyama, 2012). Research in Australia, the USA and the United Kingdom has found that a minority of adults with high-functioning ASD or Asperger's syndrome live independently (Burrows, Ford, & Bottroff, 2001;Howlin, 2003;Lawrence, Alleckson, & Bjorklund, 2010).…”
mentioning
confidence: 97%